Collaboration between Hulong Subdistrict Administrative Organization and Hulong Community on Flood Management in Pak Phanang District, Nakhon Si Thammarat Province - Sangthong, Kittisak; Rinthaisong, Idsaratt (Kasetsart Journal of Social Sciences, 2015)
Findings are presented from research which studied: 1) collaboration between the Hulong Subdistrict Administration Organization (SAO) and the Hulong community on flood management, based on the disaster management cycle; and 2) factors which contributed to successful collaboration between the Hulong SAO and the Hulong community on flood management. In-depth interviews with 18 flood victims and from a focus group discussion with eight participants consisting of administrators, members of council, and officers of the Hulong SAO were also undertaken using interview forms as the research tool. It was found that the collaboration between the Hulong SAO and the Hulong community over three periods of time consisted of: 1) pre-impact phase: collaboration in terms of preparation for tools, appliances, food, shelter, domestic animals, and disaster warnings; 2) impact phase: collaboration in terms of community management, coordination, and communication; and 3) post-impact phase: collaboration in terms of damage management, aid, and recovery. The nine factors leading to success in collaboration for flood management in Pak Phanang district consisted of: capable administrators, effective communication, capacity building, knowledge development, public relations, public motivation, cultural activities encouraging safety, flood simulation, and improved accountability.